Oncological and Reproductive Outcomes After Fertility-Sparing Surgery for Stage I Mucinous Ovarian Carcinoma - Lin, Wei; Cao, Dongyan; Shi, Xiaohua; You, Yan; Yang, Jiaxin; Shen, Keng (Frontiers in Oncology, 2022)
Background: Fertility-sparing surgery (FSS) has been widely used for patients with early-stage mucinous ovarian carcinoma (MOC). However, there is limited evidence regarding the reproductive outcomes and the impact of growth pattern on oncological outcomes after FSS. This study aims to evaluate the oncological and reproductive outcomes of patients with stage I MOC after FSS. Methods: This retrospective study enrolled 159 women with unilateral stage I MOC treated at PUMCH between 1997 and 2019. Sixty-seven cases were pathologically reviewed for the growth pattern. Seventy-eight patients had FSS, defined as conservation of the uterus and at least part of one ovary, while 81 underwent radical surgery (RS). Oncofertility outcomes were compared between the groups and clinicopathological factors associated with disease-free survival (DFS) were analyzed by univariate and multivariate analyses. Patients in the FSS group were contacted to collect data on reproductive outcomes. Results: Eighteen patients developed recurrent disease during a median follow-up of 69 months, including 12 in the FSS and six in the RS group. There was one death in each group. There was no significant difference in DFS between the groups. CA125 >35 U/ml, stage IC, and incomplete staging were correlated with worse DFS according to multivariate analysis (P=0.001; P=0.012; P=0.003, respectively). There was no significant difference in DFS between patients with stage IA and stage IC1 in the FSS group, while DFS was poorer in patients with stage IC2/3 than stage IA (P=0.028). In addition, DFS was significantly poorer in patients who underwent unilateral salpingo-oophorectomy (USO) compared with those receiving USO plus staging surgery (P=0.015). There was a tendency towards poorer DFS in the infiltrative tumors compared with the expansile tumors (P=0.056). Of 23 patients who attempted to conceive, 21 (91.3%) achieved 27 pregnancies, including 26 spontaneous pregnancies and one following assisted reproductive technology. Twenty patients gave birth to 24 healthy babies, including 21 full-term and three premature births. The live-birth rate was 88.9%. Conclusions: FSS is a suitable option for young women with unilateral stage I expansile MOC, with acceptable oncological outcomes and meaningful pregnancy rates. Re-staging should be proposed in patients who undergo incomplete staging surgery.